Highly efficient green mesostructured urea functionalized on SBA-15 catalysts for selective synthesis of benzlidenemalononitrile - Appaturi, Jimmy Nelson; Johan, Mohd Rafie; Ramalingam, R. Jothi; Al-Lohedan, Hamad A. (Elsevier, 2018)
A series of urea-immobilized SBA-15 catalysts were synthesized via post grafting method using 3-chloropropyltriethoxysilane (CPTES) as the anchoring agent. The solid catalyst was characterized by PXRD, N2 adsorption-desorption, FT-IR, elemental analyzer, TEM, CO2-TPD and 29Si CP/MAS NMR. Detailed analysis of the pore size illustrated the mesoporous nature of the immobilized catalyst. The as-prepared catalyst was further evaluated in the Knoevenagel condensation reaction under different reaction conditions. Benzaldehyde was employed in the Knoevenagel condensation reaction with malononitrile. Catalytic results showed that the Urea(4.8)/SBA-15 exhibits high efficacy (98% of yield) for promoting this reaction at 40 °C and in the absence of a solvent. Under the same reaction conditions, acetylacetone led to a lower benzaldehyde conversion of 10%, whereas ethyl cyanoacetate provides up to 88% conversion. The catalyst could be recycled and reused for at least five reaction cycles with slight loss of catalytic activity.